THE ROLE OF POEMS IN DEVELOPING CRITICAL THINKING SKILL OF LOW ACHIEVING STUDENTS - Siti Aisyah; Priyanto Widodo; M. Khusni Mubarak; Endah Harumi (Widya Mandala Surabaya Catholic University, 2019)
Critical thinking is always assumed to deal with critical reading and critical writing that also involve scientific materials. Critical thinking is also judged as the thinking skill limited to smart students only, since there are complicated problems involved, namely linguistic, psychological and cognitive problems. For students with such kinds of condition and situation, they need different materials and strategies adjusted to their characteristics to develop their critical thinking skills. This research showed that low achieving students of English as a foreign language (EFL) successfully improved their critical thinking skills after having activities of the poem interpretation and analysis activities in their Reading classes. This research also proved that when they align in pursuit of critical thinking by reading poems completed with the assignments. These lead the students to engage themselves not only in joyful learning activities of reading but also in training their thinking skills. They could perform interpreting and analysing poems with reasonable points of view. By having descriptive qualitative research for several months, there were crucial factors in optimizing the best performance of the low achieving students of EFL in thinking critically, namely well-designed lesson plans, peer-learning activities, and good teacher feedbacks.